Coming Out - Frackman, Kyle 1979- (Camden House German Film Classics, 2022)
Examines the creation, context, and significance of the first and only East German feature film about homosexuality. It took forty years for East Germany's state-run studios, DEFA, to produce a feature film about homosexuality: Coming Out. The film's story seems radically ordinary today: a young teacher, Philipp, is gay but cannot accept the truth about his sexuality. He starts a relationship with a fellow teacher, Tanja, but falls in love with a man he meets, Matthias, whose confidence in his own self-understanding is alluring for him as well as a challenge. Acclaimed director Heiner Carow created a film that shows the difficulties, both internalized and external, that queer people faced in East Germany. In a quirk of history, Coming Out premiered in German theaters on November 9, 1989, the very night on which the Berlin Wall was opened, which meant the film was initially overshadowed, to say the least, by the earthshaking political events. Yet it remains a popular film and is regularly screened around the world, including prominently at queer film festivals. Kyle Frackman's book examines the film in both the late East German context of its creation and the international context of its reception. This book is openly available in digital formats under Creative Commons license CC BY-NC